ADNP Controls Gene Expression Through Local Chromatin Architecture by Association With BRG1 and CHD4 - Sun, XiaoYun; Yu, WenJun; Li, Li; Sun, YuHua (Frontiers in Cell and Developmental Biology, 2020)
ADNP (Activity Dependent Neuroprotective Protein) is proposed as a neuroprotective protein whose aberrant expression has been frequently linked to rare neural developmental disorders and cancers, including the recently described neurodevelopmental Helsmoortel-Van der Aa syndrome. Recent studies have suggested that ADNP functions as an important chromatin regulator. However, how ADNP-regulated chromatin mechanisms control gene expression and stem cell fate commitment remains unclear. Here we show that ADNP interacts with two chromatin remodelers, BRG1 and CHD4. ADNP is required for proper establishment of chromatin accessibility, nucleosome configuration, and bivalent histone modifications of developmental genes. Loss of ADNP leads to enhancer over-activation and increased ratio of H3K4me3/H3K27me3 at key primitive endoderm (PrE) gene promoters, resulting in prominent up-regulation of these genes and priming ES cell differentiation toward endodermal cell types. Thus, our work revealed a key role of ADNP in the establishment of local chromatin landscape and structure of developmental genes by association with BRG1 and CHD4. These findings provide further insights into the role of ADNP in the pathology of the Helsmoortel-Van der Aa syndrome.